CRIg mediates early Kupffer cell responses to adenovirus. Issue 2 (1st February 2013) - He, Jeannie Q.; Katschke, Kenneth J.; Gribling, Peter; Suto, Eric; Lee, Wyne P.; Diehl, Lauri; Eastham‐Anderson, Jeffrey; Ponakala, Anusha; Komuves, Laszlo; Egen, Jackson G.; van Lookeren Campagne, Menno
Abstract : CRIg plays a critical role in regulating Kupffer cell function and survival in response to adenovirus infection. Abstract : Whereas adenoviral vectors are known to activate the complement cascade, leading to fixation of C3 proteins to the viral capsid, the consequences of this activation for viral clearance from the circulation are not known. Liver KCs, the macrophage population responsible for early uptake and elimination of many blood‐borne pathogens, express CRIg, a complement receptor for C3 proteins. Here, we find that CRIg is important for the early elimination of C3‐coated adenoviral vectors from the sinusoidal bloodstream by KCs. We further demonstrate that by acting as a critical receptor for adenovirus phagocytosis, CRIg plays an important role in regulating virus‐induced KC death and depletion of these cells from the liver sinusoidal lumen. Our study thus identifies a critical pathway regulating KC function and survival in response to systemic viral infection.